Aktivitetsmönster och boskapspredation hos lejon (Panthera leo) i förhållande till olika miljöfaktorer - Karjel, Elvira (SLU/Dept. of Animal Environment and Health (until 231231), 2022)
The lion is one of few large predators that have suffered terrible population losses over the past two decades. As a result of this lions are now considered vulnerable on the IUCN Redlist, and on their way towards becoming endangered. The estimated number of individuals is approximately 32 000 today, and the majority are found in Africa. The main cause of the population decline is the growth of the human population. Through an increase of the human population the land use by humans’ have subsequently expanded, which has resulted in large habitat loss for lions. Habitat loss in correlation with large territories has caused the frequency of human-wildlife conflicts to rise. With the majority of the community being livestock herders, the most prevalent human-wildlife conflict between humans and lions is livestock predation. Livestock predation often results in economic loss for the herder. Hunting has therefore become a way for them to enact their revenge on the lions that killed the livestock. Because of this it is of the utmost importance to find what affects lions from day to day and how that influences livestock predation. The aim of this study was for this reason to examine the activity pattern of lions and how this can be affected by different moon phases, cloud cover and precipitation. The effects of moon phase, cloud cover and precipitation on livestock predation was also analyzed in this study. The study was executed using motion activated camera traps in Ol Pejeta Conservancy and reports about deaths of cattle caused by lions in the conservancy. The results showed that the only significant effect that moon phase had, was in relation to livestock predation where predation during the day was the only variable influences. However, both cloud cover and precipitation were found to cause a difference in activity in lions, with increased activity during less cloud cover or less precipitation. In relation to the predation on cattle there was no evidence to support that precipitation had an effect. Nevertheless, high cloud cover portion was found to result in higher livestock predation during the night. In conclusion it was found that all the environmental factors affected the activity of lions or livestock predation in some way. Although, an increase in activity did not always indicate a subsequent rise in predation. By using these findings, we can find ways of preventing and mitigating human-wildlife conflicts.